Evaluation of three physical mixing methods of nanoparticles to orthodontic primer - Rawof R Al Tuma; Yassir A Yassir; Grant T McIntyre (College of Dentistry/ University of Baghdad, 2024)
Background: Demineralization and white spot lesions are the most common complications in fixed orthodontic treatment. It is useful to enhance the remineralization properties of the orthodontic primer by the addition of remineralizing agents. Fluoride and calcium are regarded as the main component of enamel fluorohydroxyapatite crystals. This pilot study compared three mixing methods of calcium fluoride nanoparticles (nCaF2) with conventional orthodontic primer (Transbond XTTM) to develop a primer with enamel remineralization properties. Materials and methods: The nanoparticles were added to Transbond XTTM primer to form 20% (w/w) of the final solution. Three dark plastic bottles were prepared and stored until mixing. The first sample was mixed by a Vortex machine, the second was mixed with an electric agitator, and the third one was mixed with a customized plastic spatula adapted to a dental engine and a straight handpiece. Cured blocks of the developed primer were prepared and were examined for homogeneity, cracks, and agglomeration of the nanoparticles within the primer using Field Emission Scanning Electron Microscopy (FESM). Results: The third Sample showed a continuous distribution of nanoparticles with no apparent cracks or agglomeration of nanoparticles. In contrast, a higher agglomeration was seen in the first sample than in the other two. Conclusion: Mixing of nCaF2 with Transbond XTTM orthodontic primer was best achieved by the customized plastic spatula adapted to a dental engine compared to Vortex and electric agitator machines.